Effectiveness of Innovative Learning Media To Improve Counting Ability In Early Childhood - Yulianti Tri Widiastuti; Rejo Kirono (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
The learning element that must be considered is the learning media. One way that teacher can do is to use learning media that can attract children's attention so that the ability to count will accompany it. One of the learning media that can be used is the busy book learning media. The Busy Book is made of flannel with bright and varied colors and is safe for children in daily activities. Learning media that is quite interesting for children, especially at the age of 5-6 years is busy book learning media. The purpose of this study was to determine the effectiveness of busy book learning media to improve numeracy skills in early childhood. The research was conducted through experiments to 16 students in Class B. The data was collected through an oral counting test. The data analysis technique was carried out through a difference test with the Wilcoxon Signed Rank Test. The results showed that there was a significant difference in the students' counting ability before after the implementation of learning using busy book media. These results indicate that the use of innovative learning media is effective in increasing numeracy skills at an early age. Keywords: learning media, innovative learning, counting ability